Genetic parameters and identification of genomic regions and candidate genes associated with vaginal discharge score in Holstein cattle based on genomic and transcriptomic analyses - Junxing Zhang; Liyun Han; Hui Sheng; Hailiang Zhang; Luiz F. Brito; Shanshan Li; Guoshang Ji; Xingang Dan; Bei Cai; Yamei Hu; Yachun Wang; Yun Ma (Journal of Dairy Science)
ABSTRACT: A healthy uterine environment is essential for establishing and maintaining pregnancy and normal embryo development after insemination. In this context, the primary objectives of this study were to assess the genetic background of vaginal discharge score (VDS) traits during the voluntary waiting period in Holstein cows and to identify genomic regions and candidate genes influencing postpartum uterine health based on the integration of phenotypic, genomic, and transcriptomic datasets. Genetic parameters of 5 VDS traits defined according to lactation stage (VDS1, VDS2, VDS3, VDS4, and VDS5) were estimated based on VDS records from 64,241 Holstein cows that calved between 2019 and 2023 and genomic information from 2,489 cows. The GWAS were performed aiming to identify genomic regions associated with VDS traits. Differentially expressed genes and modular genes were obtained through RNA sequencing (RNA-seq) data of uterine secretion from 6 healthy and 6 diseased cows. The VDS traits had low-h2 estimates ranging from 0.006 ± 0.002 to 0.081 ± 0.011. Among the VDS traits, there were relatively strong genetic correlations between VDS1 (0–14 DIM) and metritis (0.678–0.763), as well as VDS3 (29–55 DIM) and endometritis (0.579–0.628). A total of 190 genes harboring 32 significant SNPs were identified as candidate genes regulating VDS in primiparous cows. The candidate genes identified were significantly enriched for pathways involved in cytokine-cytokine receptor interaction, mitogen-activated protein kinase signaling, and oxytocin signaling. Based on RNA-seq data of uterine secretions, 2,803 differentially expressed genes and 3,570 modular genes were identified. Furthermore, 7 genes were identified based on GWAS, differential gene expression, and weighted gene coexpression network analysis. The VSTM1, IL10RA, FXYD5, C2CD5, CETN4, ALS2CL, and PBX1 genes were considered to be the most promising candidate genes influencing postpartum uterine health in Holstein cows. This study provides novel insights on the genetic background of postpartum uterine health in Holstein cows. The results obtained can contribute to further refinements of selection indexes for improving uterine health and fertility in dairy cattle.